DEVIATION OF MAXIMS IN ENGLISH ADVERTISEMENTS - Gurendi Wiwoho (Universitas 17 Agustus 1945 Semarang, 2023)
Advertising language has certain features, Those are persuasive and provocative. The writer was interested in conducting a research concerning the advertising language and analyzed it by using the pragmatic approach. The analysis only focuses on the illocutionary act and the application of cooperative principles. This paper contains the theoretical background of pragmatics and the pragmatic analyses on English advertisements. The results of the research shows that: (1) the English reading advertisement can be called the provocative news with the reason that the news contains not only the information in the formof a report but also a tendency to offer products of goods and services; (2) the reading advertising studied in the discussion contains the kinds of illocutionary act and the cooperative principles; (3) the illocution power in the words of the English advertisement has the kinds of direct illocution and indirect illocution; and (4) the obedience and deviation of the cooperative principles occur in the advertising to propagate the products and services advertised.Â Keywords: pragmatic, advertising, illocutionary act, cooperative principles, utterance.